Interaksi Sosial Antarumat Beragama di Perumahan Bumi Dalung Permai Desa Dalung, Kuta Utara, Badung - Aliffiati, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Bumi Dalung Permai is an housing complex built in theearly 1990s in Badung Regency. Accredited member of anBumi Dalung Permai public buldingt set of background,it is an the people of heterogen and multicultur, theybe possessed of different set of background etnick, joboccupation, level in society, tradition and religion.The living dynamics interfaith in Bumi Dalung Permaipublic bulding relatived settlement by agreement. Theliving dynamics Bumi Dalung Permai public bulding havetwo. The living dynamics intern that is the same interfaith,conflict and cooperation will it do. Conflict and cooperationproceed from different set an understating of religion.The living dynamics extern have enthusiasm united andtolerance. Conflict take palace beetween Hinduism withMuslims proceed from different set of interest. Conflictsolution by medition and negotiationally so that conflictget muffied. Social interaction beetween the membersof religious community in Bumi Dalung Permai publicbulding in a general manner go well and harmonic, bymeans of celebration ritual ceremony and tradition, socialactivity, tradisi ngejot adaption be in possession conformitywith, symbols that is to be a means by members ofreligious community with the result that communicationdevice, public area available as interaction area which is allaccredited member of an association in a together manneralthough communitation.
Keywords: social dynamics; social interaction; conflict